The invisible enemy: Fighting the plague in early modern Italy. (27th July 2020) - Henderson, John
Abstract: This brief survey article examines the strategies to cope with plague in early modern Italy, often hailed at the time and by historians as the country that provided the model for public health policies in other parts of Europe and even formed the basis for policies in subsequent centuries. The study is organised according to three mains themes that are familiar today, containment, mitigation, quarantine, which also lay at the heart of plague strategies in early modern Europe. The starting point will be to determine which measures contemporaries believed were particularly efficacious, through the lens of their own understanding of disease. Then, by juxtaposing recent historical and demographic studies, I examine the application and effectiveness of public health measures in a country that was comprised of a series of larger and smaller states. In the process, I seek to raise wider questions about whether it was human intervention or non‐human factors, in particular regional ecology, that determined the impact of plague in particular areas.